Uptake and bioaccumulation of Cry toxins by an aphidophagous predator. (February 2016) - Paula, Débora P.; Andow, David A.
Abstract: Uptake of Cry toxins by insect natural enemies has rarely been considered and bioaccumulation has not yet been demonstrated. Uptake can be demonstrated by the continued presence of Cry toxin after exposure has stopped and gut contents eliminated. Bioaccumulation can be demonstrated by showing uptake and that the concentration of Cry toxin in the natural enemy exceeds that in its food. We exposed larvae of the aphidophagous predator, Harmonia axyridis, to Cry1Ac and Cry1F through uniform and constant tritrophic exposure via an aphid, Myzus persicae, and looked for toxin presence in the pupae. We repeated the experiment using only Cry1F and tested newly emerged adults. Both Cry toxins were detected in pupae, and Cry1F was detected in recently emerged, unfed adults. Cry1Ac was present 2.05 times and Cry1F 3.09 times higher in predator pupae than in the aphid prey. Uptake and bioaccumulation in the third trophic level might increase the persistence of Cry toxins in the food web and mediate new exposure routes to natural enemies. Highlights: Uptake and bioaccumulation of two Cry toxins by a larval coccinellid was tested. Uptake was demonstrated by presence of the toxins in pupae and adults. Bioaccumulation was shown by higher toxin concentration in pupae than prey. Cry1Ac was present 2.05× and Cry1F 3.09× higher in predator pupae than prey. This might increase persistence of Cry toxins in food webs with new exposure routes. Abstract : Immatures of the predaceous coccinellid Harmonia axyridis can uptake and bioaccumulate Cry toxins delivered via their aphid prey.